Computer Games and New Media Cultures: a Handbook of Digital Games Studies - Fromme, Johannes; Unger, Alexander (Springer, 2012)
This handbook aims to reflect the relevance and value of studying digital games, now the subject of a growing number of studies, surveys, conferences and publications. As an overview of the current state of research into digital gaming, the 42 papers included in this handbook focus on the social and cultural relevance of gaming.
Keywords: 1-Jeux vidéo; 5-Auteur.rice PANDC; _Nettoyé